Reduction of Cypermethrin Residue in Jambal Roti of Giant Catfish (Arius Thalassinus Ruppell) - Nursinah Amir; Eddy Suprayitno; Hardoko Hardoko; Happy Nursyam (JURNAL PERIKANAN DAN KELAUTAN, 2018)
Jambal Roti is a dry-salted fish product made from Giant Catfish (Arius thalassinus Ruppell) with a bread-like texture when fried. This product was found to contain cypermethrin residue exceeding the BMR maximum limit determined by SNI and CAC. This study aimed to determine the best processing method to minimize the residue of cypermethrin in Jambal Roti products. A completely randomize experimental methosd was employed with five treatments and the replicates of each treatment. Treatments applied were A (washing the Jambal Roti for 1 minutes with running tap water), B (soaking in warm water at 50 ° C for 15 minutes), C (frying at 170 ° C for 10 minutes), D (washing with running tap water then fried) And E (soaking then fried). The residue of cypermethrin was analyzed gas chromatography prior and after the experimental treatments. Results indicated that all treatments were capable of reducing the cypermethrin content of the Jambal Roti. The highest percentage of the cypermethrin residue reduction was achieved by the treatment D in residual residuals in treatment D (washing with running tap water and then fried).